Implementasi Pembelajaran Case Method dalam Meningkatkan Keterampilan Berpikir Kritis pada Mata Kuliah Pemasaran Jasa - Suswita Roza; Erida Erida; Ade Perdana Siregar (Universitas Batanghari Jambi, 2022)
The world of education is expected to prepare human resources who can solve problems, are critical and innovative. The activeness of students has an important role in the service marketing learning process so that it can stimulate critical thinking. Project-based learning model is more effective in improving students' critical thinking skills compared to conventional learning. The purpose of this study is to examine the effect of applying a project-based learning model with a case-solving method in developing critical thinking skills in students who teach service marketing courses. The research method used is descriptive as an evaluation stage. Descriptive analysis is used to describe as an evaluation with critical thinking skills qualifications for students who take courses in service marketing. The project-based learning model in service marketing courses using the case method can improve students' ability to think critically, this condition is very much needed in today's uncertain conditions. Consumer behavior towards services is always changing, where business people and academics are required to be able to think critically in order to innovate to meet consumer needs.